2009
DOI: 10.1519/jsc.0b013e3181c03548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Linear and Daily Undulating Periodized Resistance Training to Increase Strength

Abstract: To determine the most effective periodization model for strength and hypertrophy is an important step for strength and conditioning professionals. The aim of this study was to compare the effects of linear (LP) and daily undulating periodized (DUP) resistance training on body composition and maximal strength levels. Forty men aged 21.5 +/- 8.3 and with a minimum 1-year strength training experience were assigned to an LP (n = 20) or DUP group (n = 20). Subjects were tested for maximal strength in bench press, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 23 publications
3
53
1
13
Order By: Relevance
“…These results corroborate a previous study from Prestes et al (2009b) who compared the effects of daily UP and LP in 40 experienced RT men and found no significant changes in body composition after 12 weeks of training. Although the repetition maximum zones were similar when compared with this study, the methodology and increments for LP and UP were different.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results corroborate a previous study from Prestes et al (2009b) who compared the effects of daily UP and LP in 40 experienced RT men and found no significant changes in body composition after 12 weeks of training. Although the repetition maximum zones were similar when compared with this study, the methodology and increments for LP and UP were different.…”
Section: Discussionsupporting
confidence: 92%
“…Although the repetition maximum zones were similar when compared with this study, the methodology and increments for LP and UP were different. In addition, contrary to Prestes et al (2009b), this study used a more sensitive method to evaluate changes in body composition. These results may be explained by the lack of a more rigid dietetic control and the absence of combined aerobic training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has limitations to increase lean body mass, the principal mechanism by which strength is enhanced. It is thought that long periods of low volume, high intensity training characterized by linear periodization models resulted in less favorable hypertrophic adaptations and may induce neural fatigue [19]. Found that NLP induced a greater percent increase in maximal strength for the bench press, the 45 0 leg press, and the arm curl after 12 weeks of training compared with LP (NLP 25.08, 40.61, and 23.53% vs. LP 18.2, 24.71, and 14.15%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted to evaluate the influence of DUP in resistance training programs showed greater increases in muscle strength than linear or classical periodization (Rhea et al, 2002;Prestes et al, 2009). These data demonstrate that performing daily program alterations can be more effective than linear periodization.…”
Section: Discussionmentioning
confidence: 99%